Analisis Motivasi Kerja Pustakawan Open Library Telkom University dalam Menyelenggarakan Layanan Pesan-Antar - Damayanti, Alfina (Ilmu Informasi Perpustakaan dan Kearsipan, 2023)
The delivery service at Telkom University's open library was developed and introduced generally since the Covid-19 pandemic which resulted in various limitations in the service and learning activities of the Telkom University academic community. This research aims to determine the motivation of librarians in providing delivery services and document delivery services at the Telkom University Open Library. The research method used is qualitative with a case study approach. Data collection techniques were carried out through interviews, observation, documentation and literature study. The results of the research show that the motivation for librarians to provide delivery services and document delivery services at Telkom University's Open Library is as a form of librarian worship, the desire to help users, a form of librarian responsibility, realizing excellent service, adequate facilities and infrastructure, as well as having a strong leadership role. provide direction and support to librarians.